Mother Tongue Interference in English Use at an Islamic Boarding School - Denti Listiana; Otong Setiawan Djuharie (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Mother tongue interference is a common phenomenon in foreign language acquisition, especially in bilingual and multilingual learning environments. In Indonesian Islamic boarding schools (pesantren), students are encouraged to use foreign languages such as English and Arabic in daily communication; however, intensive contact between languages often results in interference from students’ first language when they use English. This study aims to investigate the forms of mother tongue interference in English usage among eleventh-grade students at an Islamic boarding school and to identify the dominant types of interference that occur. This research employs a qualitative descriptive approach, with data collected through written questionnaires and documentation of students’ daily English utterances. The data were analyzed by classifying and describing interference based on linguistic levels, including lexical, morphological, syntactic, phonological, and pragmatic aspects. The findings show that mother tongue interference appears in various forms, with lexical and syntactic interference being the most dominant. Students frequently insert particles, vocabulary, and sentence structures from their first language into English utterances, indicating a strong influence of the mother tongue system. This condition suggests that students’ English proficiency remains at the interlanguage stage. These findings inform contextual teaching.